Effect of an acceptance and commitment therapy workshop on parents of children with aggressive behavior at a mental health hospital in Lima, year 2014-2015 - Caycho Salazar, Flower de María de Jesús (2022)
We evaluated the effect of an assertiveness workshop focused on Acceptance and Commitment therapy (ACT) aimed at parents in achieving change in their children's aggressive behavior compared to a standard Cognitive-Behavioral intervention (CBT), that is, find out if an intervention based on ACT or a standard Cognitive-behavioral treatment is more effective, from a statistical analysis point of view, as well as its clinical relevance. The experimental population consisted of 15 parents, divided into three groups: control, ACT and CBT. An A-B univariate multiconditional multigroup experimental design was used. In the ACT workshop, training was proposed for parents on how to manage child behavior through assertiveness guidelines under the contextual therapeutic model, throughout sessions planned under the three basic components of this intervention: acceptance, values and distance.The results showed that the subjects who received the ACT workshop modified inappropriate behaviors, however, no significant differences were found between the CBT and ACT groups.